2012
DOI: 10.4161/rna.20187
|View full text |Cite
|
Sign up to set email alerts
|

New kid on the ID block

Abstract: Polyadenosine RNA binding proteins (Pabs) play critical roles in regulating the polyadenylation, nuclear export, stability and translation of cellular RNAs. Although most Pabs are ubiquitously expressed and are thought to play general roles in post-transcriptional regulation, mutations in genes encoding these factors have been linked to tissue-specific diseases including muscular dystrophy and now intellectual disability (ID). Our recent work defined this connection to ID, as we showed that mutations in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…This included changes in CHGA, EPO, PAP, PTPA, TLE1, RN149 and TRIPB. The others have roles in immune system function (IgA, IL-3, TENA, CLC4K [ 49 , 50 ]), regulation of brain-specific mRNAs (ZC3HE [ 51 ]) transfer RNA processing (MRRP1 [ 52 ]) or cell adhesion and mobility (ARMC3 [ 53 ]). Previous studies have shown a reduction of IgA levels in subgroups of people with ASC although the study design did not test for sex differences [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…This included changes in CHGA, EPO, PAP, PTPA, TLE1, RN149 and TRIPB. The others have roles in immune system function (IgA, IL-3, TENA, CLC4K [ 49 , 50 ]), regulation of brain-specific mRNAs (ZC3HE [ 51 ]) transfer RNA processing (MRRP1 [ 52 ]) or cell adhesion and mobility (ARMC3 [ 53 ]). Previous studies have shown a reduction of IgA levels in subgroups of people with ASC although the study design did not test for sex differences [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZC3H14 (Zinc Finger CCCH-Type Containing 14) is an evolutionarily conserved, ubiquitously expressed polyadenosine RNA-binding protein (Leung et al, 2009). Mutations in the ZC3H14 gene cause an autosomal-recessive, non-syndromic form of intellectual disability (Al-Nabhani et al, 2018; S. Kelly et al, 2012; Pak et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the ZC3H14 gene cause autosomal-recessive intellectual disability, indicating that ZC3H14 plays a critical role in the brain (50,51). Like Nab2, ZC3H14 regulates poly(A) tail length (49).…”
mentioning
confidence: 99%